PROSES PRODUKSI PROGRAM SIARAN KUMPULAN INSPIRASI SAHABAT DI RRI PRO 2 YOGYAKARTA - Dian Esti Nurati, Buddy Riyanto, Mitha Rizkyta Saraswati, (Solidaritas, 2018)
AbstractProgram broadcast âSiaran Kumpulan Inspirasi Sahabatâ is one of the programs in RRI Pro 2 Yogyakarta, this program is usually called the program of Kisah. The âSiaran Kumpulan Inspirasi Sahabatâ Â program is a program that aims to inspire RRI Pro 2 Yogyakarta listeners. Media radio is the main capital exposure of radio to the audience and the stimulation connected to the audience. The success of a radio station is inseparably influenced by the program broadcasted, such as the program broadcast âSiaran Kumpulan Inspirasi Sahabatâ in RRI Pro 2 Yogyakarta.The problem in this research is how the production process of the program âSiaran Kumpulan Inspirasi Sahabatâ in RRI Pro 2 Yogyakarta. With the purpose of research is to describe the production process of the program broadcast âSiaran Kumpulan Inspirasi Sahabatâ Â in RRI Pro 2 Yogyakarta. âSiaran Kumpulan Inspirasi Sahabatâ bring resources who will make the recording process in order to get good results. The program of âSiaran Kumpulan Inspirasi Sahabatâ is broadcasted directly without presenting the speakers, the speakers present only with the recording in other words only played the recording.The theory used in this research is the Production Process of Broadcast Program by using theory from Morrisan.This research method is descriptive qualitative research type, data collecting technique using interview, observation and documentation. As for the validity of data using triangulation of data, in this study the authors use interactive data analysis technique is the analysis model that requires 3 components of data reduction, data presentation and conclusion.The result of the research of the production process of the âSiaran Kumpulan Inspirasi Sahabatâ is known that the pre-program production of the story is the discovery of an idea inspired by Kick Andys broadcast program on Metro TV and in pre production is also determined for the selection of resource persons. The next process is a production process where in this process there are 3 stages of the resource person will conduct a recording session of his personal story, then will enter the editing and mixing stage conducted by the team RRI Pro 2 Yogyakarta. The last process is post-production that will perform the evaluation, evaluation in the story program is done twice before and after the show story program.The conclusion of this research is the production process of broadcast program of âSiaran Kumpulan Inspirasi Sahabatâ Â well organized, in the process of editing and mixing done carefully so as to reduce the noice and obstacle in recording process. So it becomes interesting, engaging, and improving good results for the listener.Keywords: Radio, Production Process, Program Kisah